Hubungan antara Aktivitas Fisik Wanita Prakonsepsi dan Kejadian Diabetes Melitus Gestasional: Literature Review - Mahda Putri Kusumawardhani; Anisa Lailatul Fitria (Media Gizi Kesmas, 2025)
Background: Glucose intolerance is a hallmark of gestational diabetes mellitus in the early stages of pregnancy.  Maternal and perinatal problems such as preeclampsia, gestational hypertension, cesarean delivery, macrosomia, and still birth are frequently caused by gestational diabetes mellitus. Another treatment option for preventing gestational diabetes mellitus is exercise, both before and during pregnancy. Physical activity plays a role in regulating glucose homeostasis, indirectly or directly, and impacts insulin sensitivity through several mechanisms. Objectives: This study to assemble strong evidence regarding the relationship between a woman's preconception or prenatal physical activity and her risk of gestational diabetes mellitus. Methods: This research was conducted through a systematic literature review using Google Scholar, EMBASE, MEDLINE, ScienceDirect, and PubMed, compiled according to the PRISMA guidelines. The literature search used the PICO framework with inclusion and exclusion criteria and found seven studies that were included. Results: The results showed that physical activity before or in early pregnancy, such as walking, jogging, cycling, aerobics, swimming, yoga, etc., which routinely performed, reduced the risk of gestational diabetes mellitus. When doing physical activity, muscles will use glucose to reduce stored glucose. In filling the glucose deficiency, the muscles take blood glucose, causing blood glucose to decrease so that it can control one's blood sugar. The best strategy to reduce the risk of gestational diabetes mellitus is to be physically active both before and throughout pregnancy. Conclusions: Exercise during preconception and the first few months of pregnancy lowers the risk of developing gestational diabetes mellitus.